The Herbal Combination of Radix astragali, Radix angelicae sinensis, and Caulis lonicerae Regulates the Functions of Type 2 Innate Lymphocytes and Macrophages Contributing to the Resolution of Collagen-Induced Arthritis - Feng, Guiyu; Li, Dongyang; Liu, Juan; Sun, Song; Zhang, Pingxin; Liu, Wei; Zhang, Yingkai; Meng, Boyang; Li, Jinyu; Chai, Limin (Frontiers in Pharmacology, 2022)
Type 2 innate lymphocytes (ILC2s), promoting inflammation resolution, was a potential target for rheumatoid arthritis (RA) treatment. Our previous studies confirmed that Radix Astragali and Radix Angelicae Sinensis could intervene in immunologic balance of T lymphocytes. Caulis Lonicerae also have anti-inflammatory therapeutic effects. In this study, the possible molecular mechanisms of the combination of these three herbs for the functions of ILC2s and macrophages contributing to the resolution of collagen-induced arthritis (CIA) were studied. Therefore, we used Radix Astragali, Radix Angelicae Sinensis and Caulis Lonicerae as treatment. The synovial inflammation and articular cartilage destruction were alleviated after herbal treatment. The percentages of ILC2s and Tregs increased significantly. The differentiation of Th17 cells and the secretion of IL-17 and IFN-γ significantly decreased. In addition, treatment by the combination of these three herbs could increase the level of anti-inflammatory cytokine IL-4 secreted, active the STAT6 signaling pathway, and then contribute to the transformation of M1 macrophages to M2 phenotype. The combination of the three herbs could promote inflammation resolution of synovial tissue by regulating ILC2s immune response network. The synergistic effects of three drugs were superior to the combination of Radix Astragali and Radix Angelicae Sinensis or Caulis Lonicerae alone.